P04.15 Autophagy induction following TTFields application serves as a survival mechanism mediated by AMPK signaling. (19th September 2018) - Porat, Y; Shteingauz, A; Voloshin, T; Schneiderman, R; Giladi, M; Kirson, E; Weinberg, U; Kinzel, A; Palti, Y
Abstract: Background: Tumor treating fields (TTFields) are an approved treatment modality for patients with glioblastoma, delivered via noninvasive application of low-intensity, intermediate-frequency, alternating electric fields. TTFields were shown to induce abnormal mitosis, aneuploidy, and increased cell granularity, which are often associated with enhancement of autophagy. In this work, we evaluated the possible effect of TTFields on regulation of autophagy in glioma cells Material and Methods: Cells were treated with TTFields using the inovitro TM system. Cellular granularity was evaluated using flow cytometry. Autophagy was monitored by quantifying levels of lipidated Microtubule Associated Protein Light Chain 3 (LC3-II), in the presence and absence of the lysosomotropic agent and autophagy inhibitor chloroquine (CQ), using immunoblotting and immunofluorescence microscopy. Transmission Electron Microscopy (TEM) was used to visualize autophagosome-like structures. Time-lapse microscopy was utilized to follow autophagy induction in dividing cells. Endoplasmic reticulum (ER) stress markers were monitored by immunoblotting (for GRP78) and colorimetric assay (for intracellular ATP). Evaluating the roll of AMP activated protein kinase (AMPK) in autopagy induction was conducted by immunoblotting, as well as AMPK depletion by siRNA. Involvement of autophagy in cell fate after TTFields treatment was evaluated by producing Atg7 depleted glioma cell lines via shATG7 infection, as well as by combining TTFields with CQ, and monitoring cell growth and apoptosis by flow cytometry. Results: Significant increase in cellular granularity was demonstrated in all tested cell lines. Up-regulation of autophagy in glioma cell lines treated with TTFields was demonstrated by immunoblot analysis. Fluorescence and transmission electron microscopy demonstrated the presence of LC3 puncta and typical autophagosome-like structures in treated cells. Time-lapse microscopy revealed significant increase in the formation of LC3 puncta, specific to cells which divided during treatment. Indication of proteotoxic stress in treated cells was evident based on elevated GRP78 levels and decreased cellular ATP. Pathway analysis showed that AMPK activation regulates autophagy induction by TTFields. AMPK depletion from U87-MG cells resulted in autophagy inhibition as reflected by LC3-II levels. Depletion of either AMPK or Atg7 sensitized cells to the treatment, suggesting that cancer cells utilize autophagy as a resistance mechanism to TTFields. Combining TTFields with CQ resulted in a significant dose-dependent reduction of cell growth compared with TTFields or CQ alone. Conclusion: These results suggest that dividing cells upregulate autophagy in response to aneuploidy and ER stress induced by TTFields application and that AMPK may serve as a key regulator of this process.